Long-Term Rainfall Changes Based on Multiple Observation Stations in Eastern Nepal - Bagale, Damodar (Journal of Nepal Hydrogeological Association, 2025)
This study utilized 32 meteorological stations for rainfall analysis in Eastern Nepal over 42 years (1977–2018). It found significant fluctuations in seasonal to decadal rainfall. The study revealed that most rainfall occurs during the monsoon season. The northeastern region of Eastern Nepal has received heavier rainfall. The analysis revealed both excess and deficit monsoon rainfall events across various seasons. The year 1987 recorded the highest monsoon rainfall, while 1982 experienced the lowest. In total, eleven major deficit events and seven major excess rainfall events were identified throughout the study period. The deficit years primarily occurred between the late 1970s and mid 2010s, while the excess years were largely concentrated between the mid-1980s and early 2010s. The decadal analysis has indicated that monsoonal rainfall has decreased gradually in Eastern Nepal during the past four decades. The cause might be the changing climate indices. The Southern Oscillation Index (SOI) was strongly correlated with monsoon rainfall; this relationship was particularly pronounced in large deficit and excess events compared to the usual conditions.